Trolley Wars: The Battle of the Supermarkets - Bevan, Judi (London Profile Books, 2007)
The story of the ferocious battle for supremacy of the four main supermarket chains in Britain - Sainsbury, Tesco, Safeway and Asda. There are dynasties in decline, upstarts coming of age and those who struggle by the wayside. The story of how Tesco came from brash beginnings to challenge and finally overtake the patrician Sainsbury as the market leader in 1995 stunned the retailing world, and raised the curtain on the dramatic rise of supermarket chains in the second half of the 20th century. Behind the bare statistics of roller coaster profits and changing market shares lies a deeper tale of social change, increasing power and clashes with Government and pressure groups. The huge buying power of the supermarket chains, and the growth of edge of town shopping with vast car parking, has destroyed many small high streets along with traditional butchers, fishmongers and greengrocers. Yet their growth has been fuelled by the increase in the numbers of working women who no longer have the time or inclination to shop by foot at small outlets. The result is a love/hate relationship with their customers. The fever of competition engendered by the heads of these companies cannot be underestimated. This book goes behind the checkout till and into the boardroom to discover the true story and show what will happen next.
Keywords: Nonfiction; Business